The distribution of Sepetir lichin (Sindora coriacea) and Sepetir daun nipis (Sindora echinocalyx) in UiTM Jengka forest reserve at line 11- 20 / Khairul Hafizuddin Abdul Rahman, Muhammad Ahnaf Ahmad Sakhairi and Mohd Afiq Mat Aris - Abdul Rahman, Khairul Hafizuddin; Ahmad Sakhairi, Muhammad Ahnaf; Mat Aris, Mohd Afiq (2011)
The research is about The Distribution of Sepetir lichin (Sindora coriacea) and Sepetir daun nipis (Sindora echinocalyx) in UiTM Jengka Forest Reserve at Lines 11-20. The objective is to determine the distribution of Sepetir Iichin (Sindora coriacea) and Sepetir daun nipis (Sindora echinocalyx) in UiTM JFR at lines 11-20 and to compare the distribution on individual trees, diameter breast height (DBH), and distribution plan Sepetir lichin (Sindora coriacea) and Sepetir daun nipis (Sindora echinocalyx). From study, we found 9 individuals tree of Sepetir lichin (Sindora coriacea) and 3 individual's tree of Sepetir daun nipis (Sindora echinocalyx), the total trees we found is 12 individuals. From that individual, in DBH range 15-30cm have 4 individual trees from Sepetir lichin and 1 individual trees from Sepetir daun nipis follow by the range between 5-15cm and >45cm have 2 individual trees from Sepetir Iichin and I individual tree from Sepetir daun nipis. There have only I individual tree of Sepetir Iichin species are in range 30-45 cm.